Exclusivity in the Name of Inclusivity: Religious Moderation in Indonesia from Utopia to Oxymora - Sukri, Muhammad; Hariyanto, Ishak (MORALITY: Jurnal Ilmu Hukum, 2024)
Religious moderation is the common hope of mankind in this world; therefore, we must hate violence in any name, be it religion or humanity. We must respect, accept, respect, and uphold human values. This article explores how religious moderation as a utopian idea transformed into an oxymora-filled practice. Oxymora in the sense refers to concepts that seem to be contradictory or opposite to each other but, if examined more deeply, can produce new meanings with nuances of irony and paradox. This oxymoron can be seen in the social, political, and cultural realities in Indonesia by giving birth to the diction of "religious moderation" that aspires to inclusivity but, in reality, actually strengthens exclusivity or a certain domination. With a critical approach from Habermas' point of view, this study highlights how moderation narratives are often instrumentalized for specific interests, thus losing their communicative essence that should be inclusive and dialogical. This study also examines the role of communicative actions as formulated by Jürgen Habermas in presenting a more authentic and rational religious moderation. In this framework, religious moderation is not only understood as a normative slogan but as a dialogue process that builds consensus based on rationality, honesty, and openness between individuals and groups. The results of the study show that the failure to apply these principles often results in a form of pseudo-moderation that only deepens the polarization and dominance of power in religious discourse